Practical Considerations for Next-Generation Adjuvant Development and Translation - William R. Lykins; Christopher B. Fox (MDPI AG, 2023)
Over the last several years, there has been increased interest from academia and the pharmaceutical/biotech industry in the development of vaccine adjuvants for new and emerging vaccine modalities. Despite this, vaccine adjuvant development still has some of the longest timelines in the pharmaceutical space, from discovery to clinical approval. The reasons for this are manyfold and range from complexities in translation from animal to human models, concerns about safety or reactogenicity, to challenges in sourcing the necessary raw materials at scale. In this review, we will describe the current state of the art for many adjuvant technologies and how they should be approached or applied in the development of new vaccine products. We postulate that there are many factors to be considered and tools to be applied earlier on in the vaccine development pipeline to improve the likelihood of clinical success. These recommendations may require a modified approach to some of the common practices in new product development but would result in more accessible and practical adjuvant-containing products.